Solid oxide electrochemical cell stack, solid oxide electrochemical cell, interconnector, and method for manufacturing solid oxide electrochemical cell
By applying a protective film of high-melting point metal diffusion barrier layer and metal alloy layers such as Cu and Ag on the connectors of the solid-state oxidized electrochemical cell stack, the problem of uncertainty in the performance of the protective film in the prior art is solved, and efficient operation and performance protection of solid-state fuel cells are achieved.
Patent Information
- Application Number
- JP2023177986
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-28
AI Technical Summary
In the prior art, the protective film performance of the solid-state oxidized electrochemical cell stack is uncertain, resulting in a decrease in performance and energy loss of solid-state fuel cell.
A diffusion barrier layer containing a high melting point metal and an alloy layer containing metals such as Cu and Ag without Cr as a protective film are used to form an oxide layer by heat treatment to prevent Cr from diffusion and improve the conductivity of the oxide layer.
It effectively prevents Cr diffusion and the fall of the oxide layer, improves the conductivity of the oxide layer, protects the performance of the solid-state oxidized electrochemical cell stack, and realizes the efficient operation of the solid-state fuel cell.
Smart Images

Figure 2025068228000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid oxide electrochemical cell stack, a solid oxide electrochemical cell, an interconnector, and a method for manufacturing a solid oxide electrochemical cell, and is suitable for use in, for example, a solid oxide fuel cell stack, a solid oxide electrolysis cell stack, etc. [Background technology]
[0002] A solid oxide fuel cell (SOFC) is a fuel cell that uses an electrolyte made of solid oxide and operates at high temperatures (e.g., 600 to 1000°C), and is known as a highly efficient, long-lasting, low-cost fuel cell. The rated voltage of a single cell of a solid oxide fuel cell is about 0.7 to 0.85 V, so it is usually used as a solid oxide fuel cell stack in which multiple single cells are stacked in series via connecting members called interconnectors.
[0003] The interconnector is required to have sufficient strength at high operating temperatures of 600 to 1000°C, excellent oxidation resistance, and a thermal expansion coefficient close to that of a solid oxide fuel cell. For this reason, the interconnector is often formed using an Fe-Cr alloy such as ferritic stainless steel. Although the Cr2O3 film formed on the surface of the Fe-Cr alloy has excellent high-temperature corrosion resistance, there are problems such as the fact that if Cr volatilizes during operation, it reacts with the materials constituting the solid oxide fuel cell, causing a problem of so-called Cr poisoning, in which the performance of the solid oxide fuel cell is reduced, and the Cr2O3 film has high electrical resistance, which causes energy loss during long-term operation.
[0004] For this reason, it is common to provide a protective coating film on the surface of the interconnector. Conventionally, known examples of such coating films include one that uses a spinel-type oxide (see Patent Document 1) and one that has a protective film body containing at least one selected from spinel-type oxides and perovskite-type oxides and is dotted with a dispersed phase containing an oxide of at least one metal element selected from the group consisting of rare earth elements and zirconium (see Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2019 / 078674 [Patent Document 2] Patent Publication No. 2023-59825 [Patent Document 3] Patent No. 3857689 specification [Patent Document 4] Patent No. 3857690 specification [Patent Document 5] Patent No. 3910588 specification [Patent Document 6] Patent No. 4753720 specification [Patent Document 7] Patent No. 5905336 specification [Patent Document 8] Patent No. 5905354 specification [Patent Document 9] Patent No. 5905355 specification Summary of the Invention [Problem to be solved by the invention]
[0006] However, the performance of the protective films described in Patent Documents 1 and 2 as protective films for interconnectors is unclear.
[0007] Therefore, the problem that this invention aims to solve is to provide a solid oxide fuel cell stack and a solid oxide fuel cell, as well as such an interconnector, which are capable of exhibiting the inherent performance of the solid oxide fuel cell stack or solid oxide fuel cell by protecting the surface of the interconnector with a coating film having the performance required of a protective film.
[0008] The coating film is similarly effective for solid oxide electrolysis cell stacks and solid oxide electrolysis cells, i.e., the coating film is effective for solid oxide electrochemical cell stacks and solid oxide electrochemical cells, including solid oxide electrolysis cell stacks and solid oxide electrolysis cells, as well as solid oxide fuel cell stacks and solid oxide fuel cells.
[0009] Therefore, the problem that the present invention aims to solve is, more generally, to provide a solid oxide electrochemical cell stack and a solid oxide electrochemical cell, and such an interconnector, which are capable of exhibiting the inherent performance of the solid oxide electrochemical cell stack and the solid oxide electrochemical cell by protecting the surface of the interconnector with a coating film having the performance required of a protective film.
[0010] Another problem to be solved by the present invention is to provide a method for manufacturing a solid oxide electrochemical cell that can protect the surface of an interconnector with a coating film having the performance required of a protective film, thereby enabling the solid oxide electrochemical cell to exhibit its inherent performance. [Means for solving the problem]
[0011] In order to solve the above problems, the present invention provides: an interconnector made of an Fe-Cr alloy; A coating film provided on a surface of the interconnector, The coating film is a diffusion barrier layer containing a high melting point metal provided on a surface of the interconnector; an alloy layer on the diffusion barrier layer, the alloy layer containing at least one metal selected from the group consisting of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and substantially not containing Cr; A solid oxide electrochemical cell stack having a
[0012] This solid oxide electrochemical cell stack is shown as manufactured and before operation, after which the alloy layers transform into oxide layers.
[0013] The Fe-Cr alloy constituting the interconnector is not particularly limited as long as it has heat resistance and strength at a temperature of 1000°C or less, and the Cr content is also not particularly limited. As the Fe-Cr alloy, stainless steel is generally used. Examples of stainless steel include SUS304 (Cr content 24-26% by weight, Ni content 19-22% by weight), SUS310 (Cr content 18-20% by weight, Ni content 8-10.5% by weight), SUS430 (Cr content 18% by weight, Ni content not included), and SOFC interconnector dedicated steel Crofer22APU8 (Cr content 23% by weight, Ni content not included) (hereinafter referred to as Crofer), but are not limited thereto.
[0014] The high melting point metal contained in the diffusion barrier layer is, for example, at least one metal selected from the group consisting of Re, W, Cr, Mo, Nb, Ta, Zr and Hf, but is not limited thereto. For example, the Re-based diffusion barrier layer is described in detail in Patent Documents 3 to 9. In general, the diffusion barrier layer can improve the oxidation resistance and mechanical properties of the substrate in addition to the diffusion barrier function.
[0015] Solid oxide electrochemical cell stacks include solid oxide fuel cell stacks and solid oxide electrolysis cell stacks.
[0016] The present invention also provides an interconnector made of an Fe-Cr alloy; A coating film provided on a surface of the interconnector, The coating film is a diffusion barrier layer containing a high melting point metal provided on a surface of the interconnector; an oxide layer on the diffusion barrier layer, the oxide layer containing at least one metal selected from the group consisting of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and substantially not containing Cr except in a portion near the interface with the diffusion barrier layer; having The solid oxide electrochemical cell stack has a layer containing at least one of Cu and Ag concentrated metals in a portion of the diffusion barrier layer near the interface with the interconnector.
[0017] The solid oxide electrochemical cell stack is shown in a state after operation or in a state after manufacture and before operation in which an oxide layer is formed by oxidation. Between the diffusion barrier layer and the oxide layer, an alloy layer may be present that contains at least one metal selected from the group consisting of Cu and Ag and at least one metal selected from the group consisting of Ni, Mn, Fe and Co, and is substantially free of Cr. The oxide layer may have a variety of compositions and may be selected as required, but preferably has the highest possible electrical conductivity.
[0018] The presence of a concentrated layer of at least one of Cu and Ag in the diffusion barrier layer near the interface with the interconnector can prevent the diffusion of Cr from the Fe-Cr alloy constituting the interconnector, and can thus prevent the formation of Cr2O3 on the surface of the oxide layer. In addition, the diffusion barrier layer containing a high melting point metal has a small thermal expansion coefficient, and therefore can suppress peeling of the oxide layer during operation.
[0019] In regard to the present invention other than the above, what has been explained in relation to the above solid oxide electrochemical cell stack invention is valid, unless it is contrary to the nature of the invention.
[0020] The present invention also provides an interconnector made of an Fe-Cr alloy; A coating film provided on a surface of the interconnector, The coating film is a diffusion barrier layer containing a high melting point metal provided on a surface of the interconnector; an alloy layer on the diffusion barrier layer, the alloy layer containing at least one metal selected from the group consisting of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and substantially not containing Cr; A solid oxide electrochemical cell having a
[0021] The present invention also provides an interconnector made of an Fe-Cr alloy; A coating film provided on a surface of the interconnector, The coating film is a diffusion barrier layer containing a high melting point metal provided on a surface of the interconnector; an oxide layer on the diffusion barrier layer, the oxide layer containing at least one metal selected from the group consisting of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and substantially not containing Cr except in a portion near the interface with the diffusion barrier layer; having The solid oxide electrochemical cell has a layer containing at least one of Cu and Ag concentrated metals in a portion of the diffusion barrier layer near the interface with the interconnector.
[0022] The present invention also provides An interconnector for a solid oxide electrochemical cell stack, comprising an Fe-Cr based alloy, A coating film is provided on a surface of the interconnector, The coating film is a diffusion barrier layer containing a high melting point metal provided on a surface of the interconnector; an alloy layer on the diffusion barrier layer, the alloy layer containing at least one metal selected from the group consisting of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and substantially not containing Cr; It is an interconnector having the following structure.
[0023] The present invention also provides An interconnector for a solid oxide electrochemical cell stack, comprising an Fe-Cr based alloy, A coating film is provided on a surface of the interconnector, The coating film is a diffusion barrier layer containing a high melting point metal provided on a surface of the interconnector; an oxide layer on the diffusion barrier layer, the oxide layer containing at least one metal selected from the group consisting of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and substantially not containing Cr except in a portion near the interface with the diffusion barrier layer; having The interconnector has a layer containing at least one of Cu and Ag concentrated metals in a portion of the diffusion barrier layer in the vicinity of the interface with the interconnector.
[0024] The present invention also provides forming a first layer containing at least a high melting point metal on a surface of an interconnector made of an Fe-Cr based alloy; forming a second layer on the first layer, the second layer containing at least one metal of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and containing substantially no Cr; forming a diffusion barrier layer containing a high melting point metal from the first layer and the second layer by performing a heat treatment, and an alloy layer on the diffusion barrier layer, the alloy layer containing at least one metal of Cu and Ag and at least one metal selected from the group consisting of Ni, Mn, Fe and Co, and substantially not containing Cr; The present invention relates to a method for producing a solid oxide electrochemical cell having a
[0025] The method for forming the first layer and the second layer is selected from conventionally known methods as necessary, and specifically, an appropriate method is selected from, for example, a plating method, a slurry method, a spray method, a thermal spray method, an electron beam deposition method, etc. In one example, a plating method is used to form the first layer, and a slurry method is used to form the second layer. This method for manufacturing a solid oxide electrochemical cell further includes, as necessary, a step of forming a diffusion barrier layer and an alloy layer by performing a heat treatment after forming the first layer and the second layer, and then performing oxidation to form an oxide layer on the diffusion barrier layer, which contains at least one metal of Cu and Ag and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and does not substantially contain Cr except in a portion near the interface with the diffusion barrier layer.
[0026] In the above-mentioned invention of the solid oxide electrochemical cell, the invention of the interconnector, and the invention of the manufacturing method of the solid oxide electrochemical cell, what has been explained in relation to the above-mentioned invention of the solid oxide electrochemical cell stack is valid, so long as it is not contrary to the nature of the invention. Effect of the Invention
[0027] According to the present invention, the coating film provided on the surface of the interconnector made of the Fe-Cr alloy has a diffusion barrier layer containing a high melting point metal, and an alloy layer on the diffusion barrier layer containing at least one metal selected from the group consisting of Cu and Ag and at least one metal selected from the group consisting of Ni, Mn, Fe and Co, and substantially no Cr, so that an oxide layer can be formed from the alloy layer during or before the operation of the solid oxide electrochemical cell stack. At this time, the diffusion barrier layer can prevent oxidation of the interconnector and can prevent diffusion of Cr from the Fe-Cr alloy constituting the interconnector. The diffusion of Cr from the Fe-Cr alloy can also be prevented by a concentrated layer of at least one metal selected from Cu and Ag in the portion of the diffusion barrier layer near the interface with the interconnector. In addition, the oxide layer does not substantially contain Cr except in the portion near the interface with the diffusion barrier layer. Therefore, it is possible to prevent the formation of Cr2O3 on the surface of the oxide layer. Furthermore, this oxide layer contains at least one metal selected from the group consisting of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and therefore has higher electrical conductivity than Cr2O3. As described above, this coating film has the performance required as a protective film, and can therefore protect the surface of the interconnector, thereby enabling the solid oxide electrochemical cell stack or solid oxide electrochemical cell to exhibit its inherent performance. [Brief description of the drawings]
[0028] [Figure 1] 1 is a cross-sectional view showing an interconnector for a solid oxide electrochemical cell stack according to a first embodiment of the present invention. [Diagram 2] 1A to 1C are cross-sectional views showing a method for manufacturing an interconnector for a solid oxide electrochemical cell stack according to a first embodiment of the present invention. [Diagram 3] 1A to 1C are cross-sectional views showing a method for manufacturing an interconnector for a solid oxide electrochemical cell stack according to a first embodiment of the present invention. [Figure 4] FIG. 4 is a cross-sectional view showing a solid oxide electrochemical cell stack according to a second embodiment of the present invention. [Figure 5A] 1 is a drawing-substitute photograph showing a cross-sectional structure of a test piece of Example 1. [Figure 5B] 5B is a schematic diagram showing the measurement results of the concentration distribution of each element in the cross section of the test piece shown in FIG. 5A. [Figure 6A] 1 is a drawing-substitute photograph showing a cross-sectional structure of a test piece of Example 1 after oxidation. [Figure 6B] 6B is a schematic diagram showing the measurement results of the concentration distribution of each element in the cross section of the test piece shown in FIG. 6A. [Figure 7A] 1 is a drawing-substitute photograph showing a cross-sectional structure of a test piece of Example 2. [Figure 7B] 7B is a schematic diagram showing the measurement results of the concentration distribution of each element in the cross section of the test piece shown in FIG. 7A. [Figure 8A] 1 is a drawing-substitute photograph showing a cross-sectional structure of a test piece of Example 2 after oxidation. [Figure 8B] 8B is a schematic diagram showing the measurement results of the concentration distribution of each element in the cross section of the test piece shown in FIG. 8A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Hereinafter, a mode for carrying out the invention (hereinafter simply referred to as "embodiment") will be described.
[0030] First Embodiment [Interconnector for solid oxide electrochemical cell stacks] Fig. 1 shows an interconnector for a solid oxide electrochemical cell stack according to a first embodiment. As shown in Fig. 1, in this interconnector for a solid oxide electrochemical cell stack, a coating film 20 is provided on the upper and lower surfaces of an interconnector 10. The coating film 20 may be provided on the entire surface of the interconnector 10, including the side surfaces. The coating film 20 is composed of a diffusion barrier layer 21 provided on the surface of the interconnector 10 and an alloy layer 22 on this diffusion barrier layer 21.
[0031] The interconnector 10 is made of an Fe-Cr alloy, typically stainless steel, which is selected as necessary from among conventionally known stainless steels, including those already listed.
[0032] The diffusion barrier layer 21 contains a high melting point metal. Specifically, the diffusion barrier layer 21 may be a Re-based diffusion barrier layer, a W-based diffusion barrier layer, a Cr-based diffusion barrier layer, a Mo-based diffusion barrier layer, a Nb-based diffusion barrier layer, a Ta-based diffusion barrier layer, a Zr-based diffusion barrier layer, a Hf-based diffusion barrier layer, and the like. These diffusion barrier layers may contain one or more elements contained in the Fe-Cr-based alloy and the alloy layer 22 constituting the interconnector 10. The thickness of the diffusion barrier layer 21 is selected as necessary, and is, for example, 1 μm or more and 20 μm or less, typically 3 μm or more and 15 μm or less.
[0033] The alloy layer 22 contains at least one metal selected from the group consisting of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and does not substantially contain Cr. Here, "substantially does not contain Cr" means that Cr may be inevitably contained. The thickness of the alloy layer 22 is selected as necessary, and is, for example, 5 μm to 50 μm, typically 10 μm to 30 μm.
[0034] [Method of manufacturing interconnectors for solid oxide electrochemical cell stacks] As shown in FIG. 2, a plating layer 31 for forming a diffusion barrier layer is formed on the upper and lower surfaces of the interconnector 10 by a plating method, and then a slurry layer 32 for forming an alloy layer is formed on the plating layer 31 by a slurry method. The plating layer 31 contains at least a high melting point metal. The slurry layer 32 contains at least one metal of Cu and Ag and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and does not substantially contain Cr. The slurry layer 32 can be formed as follows. That is, a powder of at least one metal of Cu and Ag and a powder of at least one metal selected from the group consisting of Ni, Mn, Fe, and Co are put into a slurry liquid containing an organic solvent and ethanol to prepare a slurry-like powder, and the interconnector 10 on which the plating layer 31 is formed is immersed in the slurry-like powder and then pulled up, so that the slurry-like powder is applied to the entire surface of the interconnector 10. Thereafter, the interconnector 10 to which the slurry-like powder has been applied in this way is placed in an electric oven heated to, for example, 60 to 80° C., dried, and then heated. Heating is carried out in a reduced pressure atmosphere (exhaust by an oil rotary pump) or in an inert gas atmosphere using an electric furnace or a so-called fusion process using a combustion gas flame.
[0035] Next, the interconnector 10 on which the plating layer 31 and the slurry layer 32 are formed is heat-treated to form the diffusion barrier layer 21 and the alloy layer 22 from the plating layer 31 and the slurry layer 32 as shown in FIG. 1. The heat treatment is performed in a vacuum or in an inert gas atmosphere, preferably an Ar+3 vol% H2 atmosphere, at a temperature of, for example, 800°C to 1100°C for 10 minutes to 10 hours. The heat treatment may be performed in two stages at different temperatures. For example, the first stage of heat treatment is performed at a certain temperature (for example, a temperature of 900°C to 1000°C) and then the second stage of heat treatment is performed at a lower temperature (for example, a temperature of 800°C to 900°C). The diffusion barrier layer 21 is formed by a reaction between the interconnector 10 and the plating layer 31. At this time, a concentrated layer (not shown) of at least one metal selected from Cu and Ag is formed in a portion of the diffusion barrier layer 21 near the interface with the interconnector 10.
[0036] Thereafter, if necessary, the interconnector 10 having the diffusion barrier layer 21 and the alloy layer 22 formed thereon is oxidized to form an oxide layer 23 from the alloy layer 22 as shown in Fig. 3. The conditions for the oxidation are selected as necessary, but for example, the oxidation is performed in the atmosphere at a temperature of 700°C or more and 800°C or less for 10 to 150 hours.
[0037] After assembling a solid oxide electrochemical cell stack using interconnector 10 in a state before oxide layer 23 is formed, oxide layer 23 is also formed from alloy layer 22 when operation is started in a high-temperature oxidizing atmosphere.
[0038] As described above, according to the first embodiment, the coating film 20 provided on the surface of the interconnector 10 made of an Fe-Cr alloy has a diffusion barrier layer 21 containing a high melting point metal and an alloy layer 22 thereon, which contains at least one metal selected from the group consisting of Cu and Ag and at least one metal selected from the group consisting of Ni, Mn, Fe and Co, and does not substantially contain Cr. When a solid oxide electrochemical cell stack is assembled using this interconnector 10, an oxide layer 23 can be formed from the alloy layer 22 during operation of the solid oxide electrochemical cell stack. At this time, the diffusion barrier layer 21 can prevent oxidation of the interconnector 10 and can prevent diffusion of Cr from the Fe-Cr alloy constituting the interconnector 10. The concentrated layer of at least one metal selected from Cu and Ag formed in the portion of the diffusion barrier layer 21 near the interface with the interconnector 10 can also prevent diffusion of Cr from the Fe-Cr alloy constituting the interconnector 10. In addition, the oxide layer 23 does not substantially contain Cr except in the portion near the interface with the diffusion barrier layer 21. This makes it possible to prevent the formation of Cr2O3 on the surface of the oxide layer 23 during operation of the solid oxide electrochemical cell stack. Furthermore, since this oxide layer 23 contains at least one metal selected from the group consisting of Cu and Ag and at least one metal selected from the group consisting of Ni, Mn, Fe and Co, it is possible to obtain higher electrical conductivity than Cr2O3. As described above, the coating film 20 has the performance required as a protective film, and can therefore protect the surface of the interconnector 10, thereby enabling the solid oxide electrochemical cell stack to exhibit its inherent performance.
[0039] Second embodiment [Solid oxide electrochemical cell stack] Fig. 4 shows a solid oxide electrochemical cell stack according to the second embodiment. As shown in Fig. 4, in this solid oxide electrochemical cell stack, a plurality of solid oxide electrochemical cells 40 (two in Fig. 4) are connected in series via the interconnector 10 according to the first embodiment. The interconnector 10 may be in a state in which an alloy layer 22 is formed as shown in Fig. 1, or in a state in which an oxide layer 23 is formed as shown in Fig. 3, but Fig. 4 shows the former state.
[0040] When this solid oxide electrochemical cell stack is in operation, if the interconnector 10 is in a state in which the alloy layer 22 has been formed as shown in Figure 1, an oxide layer 23 is formed from the alloy layer 22, and if the interconnector 10 is in a state in which the oxide layer 23 has been formed as shown in Figure 3, the oxide layer 23 is maintained.
[0041] According to the second embodiment, a plurality of (two in FIG. 4) solid oxide electrochemical cells 40 are connected in series via the interconnector 10 according to the first embodiment, so that the interconnector 10 can be protected during operation of the solid oxide electrochemical cell stack, and the oxide layer 23 has high conductivity, so that the overall electrical resistance of the interconnector 10 can be reduced. This allows the solid oxide electrochemical cell stack to exhibit its inherent performance.
[0042] An embodiment will be described.
[0043] Test pieces made of SUS430 and Crofer were prepared.
[0044] After forming a Ni film, a Re(Ni) film, and a Ni film in that order on the surface of each test piece by plating, a mixed powder of Cu powder and Mn powder (85 wt% Cu + 15 wt% Mn) was mixed in ethanol and kneaded to form a slurry powder, which was then applied to the surface of the test piece and dried.
[0045] Next, each test piece was heated in an Ar+3 vol% H2 atmosphere at 950°C for 15 minutes, and then 60 minutes later, heated at 850°C for 10 hours.
[0046] High temperature oxidation to form the oxide layer was carried out in air at 750°C for 109 hours.
[0047] Example 1 The above method was used to heat-treat a test piece made of Crofer. A portion of the coating surface of the test piece was cut, and the cross-sectional structure was observed and the concentration distribution of each element was measured using a SEM-EDX (scanning electron microscope-energy dispersive spectroscopy) device. Figure 5A shows a cross-sectional SEM photograph, and Figure 5B shows the concentration distribution of each element along the analysis line LG1 in Figure 5A.
[0048] As shown in Figures 5A and 5B, a Re-based diffusion barrier layer and a (Cu, Ni, Mn, Fe) alloy layer are formed on the surface of the Crofer test piece. In Figure 5A, the Re-based diffusion barrier layer is described as a multi-layer DBL. The reason it is called a multi-layer DBL is because the Re-based diffusion barrier layer contains a layer with a high Re concentration and a layer with a low Re concentration. Figure 5B shows that the (Cu, Ni, Mn, Fe) alloy layer does not contain Cr.
[0049] After the test piece shown in Figure 5A was oxidized at high temperature using the method described above, a part of the coating surface of the test piece was cut, and the cross-sectional structure was observed and the concentration distribution of each element was measured using a SEM-EDX device. Figure 6A shows a cross-sectional SEM photograph, and Figure 6B shows the concentration distribution of each element along the analysis line LG2 in Figure 6A.
[0050] As shown in Figures 6A and 6B, it can be seen that a (Cu, Ni, Mn, Fe) oxide layer is formed on the Re-based diffusion barrier layer. The (Cu, Ni, Mn, Fe) oxide layer is dense and has good adhesion to the Re-based diffusion barrier layer. In the (Cu, Ni, Mn, Fe) oxide layer, Mn(Cu, Ni, Fe) oxide is formed in the outermost layer, and (Ni, Fe) oxide is formed in the inner layer, where Cr-O is concentrated. It can be seen that the (Cu, Ni, Mn, Fe) oxide layer does not contain Cr except in the area near the interface with the Re-based diffusion barrier layer. It can be seen that a Cu-enriched layer is formed in the area of the Re-based diffusion barrier layer near the interface with the test piece. The peak Cu concentration in this enriched layer is 65 atomic % or more.
[0051] Example 2 The above method was used to heat a test piece made of SUS430. A portion of the coating surface of this test piece was cut, and the cross-sectional structure was observed and the concentration distribution of each element was measured using a SEM-EDX device. Figure 7A shows a cross-sectional SEM photograph, and Figure 7B shows the concentration distribution of each element along the analysis line LG2 in Figure 7A.
[0052] As shown in Figures 7A and 7B, a Re-based diffusion barrier layer and a (Cu, Ni, Mn, Fe) alloy layer were formed on the surface of the SUS430 test piece. Figure 7B shows that the (Cu, Ni, Mn, Fe) alloy layer does not contain Cr.
[0053] After the test piece shown in Figure 7A was oxidized at high temperature using the method described above, a part of the coating surface of the test piece was cut, and the cross-sectional structure was observed and the concentration distribution of each element was measured using a SEM-EDX device. Figure 8A shows a cross-sectional SEM photograph, and Figure 8B shows the concentration distribution of each element along the analysis line LG1 in Figure 8A.
[0054] As shown in Figures 8A and 8B, it can be seen that a (Cu, Ni, Mn, Fe) oxide layer is formed on the Re-based diffusion barrier layer. The (Cu, Ni, Mn, Fe) oxide layer is dense and has good adhesion to the Re-based diffusion barrier layer. In the (Cu, Ni, Mn, Fe) oxide layer, Mn(Cu, Ni, Fe) oxide is formed in the outermost layer, (Ni, Fe) oxide is formed in the middle layer, and a Cr-O rich layer is formed in the inner layer. It can be seen that the (Cu, Ni, Mn, Fe) oxide layer does not contain Cr except in the area near the interface with the Re-based diffusion barrier layer. It can be seen that a Cu-enriched layer is formed in the area of the Re-based diffusion barrier layer near the interface with the test piece. The peak Cu concentration in this enriched layer is about 30 atomic %.
[0055] Although the embodiment and examples of the present invention have been specifically described above, the present invention is not limited to the above-described embodiment and examples, and various modifications based on the technical concept of the present invention are possible. [Explanation of symbols]
[0056] Reference Signs List 10... interconnector, 20... coating film, 21... diffusion barrier layer, 22... alloy layer, 31... plating layer, 32... slurry layer, 23... oxide layer, 40... solid oxide electrochemical cell
Claims
1. An interconnector made of an Fe—Cr based alloy; A coating film provided on a surface of the interconnector, The coating film is a diffusion barrier layer containing a high melting point metal provided on a surface of the interconnector; an alloy layer on the diffusion barrier layer, the alloy layer containing at least one metal selected from the group consisting of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and containing substantially no Cr; A solid oxide electrochemical cell stack comprising:
2. 2. The solid oxide electrochemical cell stack according to claim 1, wherein the high melting point metal is at least one metal selected from the group consisting of Re, W, Cr, Mo, Nb, Ta, Zr and Hf.
3. 3. The solid oxide electrochemical cell stack according to claim 1, wherein said Fe--Cr alloy is stainless steel.
4. 2. The solid oxide electrochemical cell stack of claim 1, wherein the solid oxide electrochemical cell stack is a solid oxide fuel cell stack or a solid oxide electrolysis cell stack.
5. An interconnector made of an Fe—Cr based alloy; A coating film provided on a surface of the interconnector, The coating film is a diffusion barrier layer containing a high melting point metal provided on a surface of the interconnector; an oxide layer on the diffusion barrier layer, the oxide layer containing at least one metal selected from the group consisting of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and containing substantially no Cr except in a portion near the interface with the diffusion barrier layer; having A solid oxide electrochemical cell stack having a layer of at least one of Cu and Ag concentrated in a portion of the diffusion barrier layer near the interface with the interconnector.
6. An interconnector made of an Fe—Cr based alloy; A coating film provided on a surface of the interconnector, The coating film is a diffusion barrier layer containing a high melting point metal provided on a surface of the interconnector; an alloy layer on the diffusion barrier layer, the alloy layer containing at least one metal selected from the group consisting of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and containing substantially no Cr; A solid oxide electrochemical cell having
7. An interconnector made of an Fe—Cr based alloy; A coating film provided on a surface of the interconnector, The coating film is a diffusion barrier layer containing a high melting point metal provided on a surface of the interconnector; an oxide layer on the diffusion barrier layer, the oxide layer containing at least one metal selected from the group consisting of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and containing substantially no Cr except in a portion near the interface with the diffusion barrier layer; having A solid oxide electrochemical cell having a layer of at least one of Cu and Ag concentrated in a portion of the diffusion barrier layer near the interface with the interconnector.
8. An interconnector for a solid oxide electrochemical cell stack, comprising an Fe—Cr-based alloy, A coating film is provided on a surface of the interconnector, The coating film is a diffusion barrier layer containing a high melting point metal provided on a surface of the interconnector; an alloy layer on the diffusion barrier layer, the alloy layer containing at least one metal selected from the group consisting of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and containing substantially no Cr; An interconnector having the following structure:
9. An interconnector for a solid oxide electrochemical cell stack, comprising an Fe—Cr-based alloy, A coating film is provided on a surface of the interconnector, The coating film is a diffusion barrier layer containing a high melting point metal provided on a surface of the interconnector; an oxide layer on the diffusion barrier layer, the oxide layer containing at least one metal selected from the group consisting of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and containing substantially no Cr except in a portion near the interface with the diffusion barrier layer; having The interconnector has a layer containing at least one of Cu and Ag concentrated metal in a portion of the diffusion barrier layer in the vicinity of the interface with the interconnector.
10. forming a first layer containing at least a high melting point metal on a surface of an interconnector made of an Fe—Cr based alloy; forming a second layer on the first layer, the second layer containing at least one metal of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe, and Co, and containing substantially no Cr; forming a diffusion barrier layer containing the high melting point metal from the first layer and the second layer, and an alloy layer on the diffusion barrier layer, the alloy layer containing at least one metal of Cu and Ag and at least one metal selected from the group consisting of Ni, Mn, Fe and Co, and substantially no Cr, by performing a heat treatment; A method for producing a solid oxide electrochemical cell comprising:
11. 11. The method for producing a solid oxide electrochemical cell according to claim 10, further comprising the step of forming, on said diffusion barrier layer, an oxide layer containing at least one metal of Cu and Ag, and at least one metal selected from the group consisting of Ni, Mn, Fe and Co, and containing substantially no Cr except in a portion near the interface with said diffusion barrier layer, by oxidizing said oxide layer after forming said diffusion barrier layer and said alloy layer by said heat treatment.
Citation Information
Patent Citations
"KANA" (japanese syllabary) and chinese character converting system
JP1984005336A
Data processing device
JP1984005354A
Access controlling system of virtual stack
JP1984005355A
Interconnector for solid oxide electrochemical cell stack and solid oxide electrochemical cell stack
JP2023059825A
ReCrNi alloy coating for diffusion barrier
JP3857689B2